Stress recovery by exposure to nature in virtual reality - Vallo, Laura Elizabeth (Kansas State University, 2017)
The purpose of this research is to identify if virtual reality environments with varying degrees of exposure to nature influence stress recovery at different rates. In 1991, environmental psychologist and architect, Rodger Ulrich, conducted a study on how varying degrees of exposure to nature influences stress recovery by showing participants videos with different levels of nature. His research concluded that participants who viewed the tapes containing scenes with higher degrees of nature recovered from stress quicker than those shown the tapes with higher degrees of human intervention. To expand on this research, it is important to understand how different mediums influence stress recovery. In particular, analyzing how fully immersive virtual reality environments influence the amount of time it takes to recover from a stressor. Virtual reality is particularly beneficial for testing as it enables variable isolation and complete environmental control. A test similar to Ulrich’s was conducted in three parts, a baseline, a stressor, and a stress recovery period. Two environments with varying degrees of human intervention were tested. The virtual reality environments were strategically designed along a same path to minimize the addition of extraneous variables. During this test, biometric data was taken in addition to stated stress levels and stated affective response. The study concluded that regardless of the environment type, participants lowered their baseline stress level. This study represents one of the firsts of its type and can serve as a valuable learning mechanism for testing in virtual reality. Results show promise for mitigating stress levels. However, it is recommended that a similar study be replicated in a more refined manor. Lessons learned from this study could be used to inform future studies investigating the effect of VR environments on stress and mental health.
Keywords: Virtual reality; Unreal engine 4; Stress recovery; Environmental psychology; Landscape architecture